Sarkasme dalam Fiilm Layar Lokal "Ambo Nai" (Kajian Stilistika) - Amus, A. Riski Gunawan; M. Agus; Yusuf, Akram Budiman; Nursalam, Nursalam (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2026)
This study aims to describe the forms of sarcasm in the dialogues of the local film Ambo Nai through a stylistic approach focusing on language aspects, including diction, language style, and sentence structure. This research employed a qualitative descriptive method with data sources taken from sarcastic dialogues in episode 16 of Ambo Nai. The data were collected through documentation techniques and analyzed by classifying utterances based on the forms of sarcasm and examining the linguistic elements contained in each utterance. The results show that sarcasm in the film appears in the forms of satire, mockery, harsh expressions, and contradictory meaning or irony. Satirical sarcasm is used to convey criticism indirectly, while mocking sarcasm is intended to demean the interlocutor. Harsh expressions are characterized by explicit and emotional utterances, whereas contradictory meanings indicate opposition between literal meaning and intended meaning. Stylistically, the use of sarcasm is dominated by harsh connotative diction, hyperbolic language styles, and spontaneous as well as expressive sentence structures. Sarcasm in the film functions as emotional expression, humor construction, and conflict reinforcement among characters